African Agency in Practice: Acquiring Agency and Institutional Change in the West African Health Organisation - Emmanuel Balogun (SAGE Publishing, 2021)
This article investigates how practitioners in the West African Health Organization (WAHO) obtain and exercise autonomous political agency in the development of regional health policy. While many process-driven accounts of African agency focus on the freedom and ability of African governments and regional organisations to act and not be acted upon, the article finds that it is necessary look within these agents to examine how they are constituted and the processes in which they acquire the capacity to be agents in their external interactions. This article shows that practitioners in WAHO rely on three institutional strategies that constitute them as agents within the organisation: networking with extra-regional partners; the inclusion of civil society in regional social policy; and the development of intra-organisational linkages to create insulation from political control. Through these strategic interactions, WAHO practitioners constitute themselves as agents within the organisation as well as autonomous agents in the broader global health theatre.